Revolutionizing Corporate Event Planning with AI: A Cost-Efficiency Strategy for BuatEvent.id - Supriyadi, Muhammad; Rianto, Yan (Institut Riset dan Publikasi Indonesia, 2025)
BuatEvent.id leverages an AI-driven platform for event planning, powered by Gemini.ai—a sophisticated NLP model with an accuracy rate of 92.5%. The system integrates multiple technologies, including PHP, Python, Golang, Flutter, and MySQL, to automate essential processes, achieving a 25% improvement in planning precision. This study aims to evaluate the role of AI in enhancing budget management and corporate event customization. By addressing the inefficiencies of conventional event planning, this platform optimizes workflows, enhances overall productivity, and offers a seamless user experience customized to cater to a wide range of client requirements. The results demonstrate a 92.5% accuracy in processing user queries and a 25% increase in event planning efficiency, highlighting the platform’s ability to deliver cost-effective and personalized solutions. These figures were obtained through internal testing using a dataset of 200 annotated user queries. The platform primarily targets corporate events, including workshops, product launches, and business meetings.For example, the system was successfully deployed during a corporate training event in Jakarta, where it reduced planning time by 30%.